Patient selection for anti-PD-1/PD-L1 therapy in advanced non-small-cell lung cancer: implications for clinical practice. (28th June 2018) - Califano, Raffaele; Lal, Rohit; Lewanski, Conrad; Nicolson, Marianne C; Ottensmeier, Christian H; Popat, Sanjay; Hodgson, Matthew; Postmus, Pieter E
Immune checkpoint inhibitors targeting PD-1 or PD-L1 represent a standard treatment option for patients with advanced non-small-cell lung cancer. However, a substantial proportion of patients will not benefit from these treatments, and robust biomarkers are required to help clinicians select patients who are most likely to benefit. Here, we discuss the available evidence on the utility of clinical characteristics in the selection of patients with advanced non-small-cell lung cancer as potential candidates for single-agent anti-PD-1/PD-L1 therapy, and provide practical guidance to clinicians on identifying those patients who are most likely to benefit. Recommendations on the use of immune checkpoint inhibitor in clinically challenging populations are also provided.